Comparison of Complications between Manual Small Incision Cataract Surgery and Phacoemulsification: Doi: 10.36351/pjo.v37i4.1317 - Bhutto, Israr Ahmed; Memon, Maria Nazish; Ali, Irshad; Soomro, Abdul Qadeem; Mirani, Abdul Haleem (Pakistan Journal of Ophthalmology, 2021)
Purpose: To compare per-operative and early post-operative complications between Manual Small Incision cataract surgery and Phacoemulsification in patients with Senile Cataract. Study Design: Quasi experimental study. Place and Duration of Study: Al-Ibrahim Eye Hospital Karachi from December 2018 to October 2019. Methods: Two hundred and seventy patients with senile Cataract were recruited for this study by convenient sampling technique. They were divided equally into two groups. Group I underwent Manual Small Incision Cataract Surgery (MSICS), whereas Group II underwent Phacoemulsification. Per-operative and early post-operative complications were recorded on day 1 in both groups. Data was analyzed using SPSS 24.0. Independent t-test was carried out with P-value of ?0.05 was considered statistically significant. Results: Mean age group – I was 54.95 ± 11.0 and in Group – II was 57.09 ± 10.59 (p = 0.546). There were 72 (53.3%) males in group – I and 74 (54.8%) in group – II with a non-significant difference (p-value > 0.01). There was significant difference for posterior capsule rupture and striate keratitis between the two groups (p = 0.031 and 0.044 respectively). Rest of the study parameters was not statistically different in the both group. None of the groups had a nucleus drop and vitreous prolapse. No significant difference was seen between the two groups concerning iris trauma (p = 0.56), wound leakage (p = 0.15) and hyphema (p = 0.32). Conclusion: There is no significant difference between per-operative and early post-operative complications between MSICS and Phacoemulsification in patients with senile cataract except posterior capsular rupture and striate keratopathy which were more common in phacoemulsification group. Key Words: Cataract, Senile Cataract, Phacoemulsification, Small Incision Cataract Surgery.